Nurses’ perceptions of individualized care: an international comparison - Efstathiou, Georgios; Lemonidou, Chryssoula; Papastavrou, Evridiki; Da Luz, Maria Deolinda Antunes; Idvall, Ewa; Berg, Agneta C.; Acaroglu, Rengin; Şendir, Merdiye; Kanan, Nevin; Sousa, Valmi D.; Katajisto, Jouko K.; Valimaki, Maritta; et al. (My University, 2011)
Aim.  This paper is a report of a study of internationally-based differences in nurses’ perceptions of individualized care in orthopaedic surgical in-patient wards. Background.  Individualized care is valued in healthcare policy, practice and ethical statements as an indicator of care quality. However, nurses’ assessments of individualized care are limited and comparative cross-cultural studies on individualized nursing care are lacking. Methods.  A descriptive comparative survey was used to sample orthopaedic surgical nurses (n = 1163) working in 91 inpatient wards in 34 acute hospitals in Finland, Cyprus, Greece, Portugal, Sweden, Turkey and the United States of America. Data were collected between March and November 2009 using the Individualized Care Scale-Nurse and analysed using descriptive and inferential statistics. Results.  Nurses in different countries perceived that they supported patients’ individuality generally and provided individualized care during nursing activities. Although the highest scores were in support of patients’ individuality in the clinical situation both through nursing provision and nurses’ perceptions of individuality, there were between-country differences within these scores. Generally, the Greek and American nurses gave the highest scores and the Turkish, Cypriot and Portuguese nurses the lowest. Conclusions.  Between-country differences found may be attributed to differing roles of nurses, care processes, healthcare systems and/or the ways nursing care is defined and organized. As this was the first time the Individualized Care Scale-Nurse was used in an international context, the results are formative and indicate the need to continue studies in this area.
Keywords: Nursing; Nurses; Cross-cultural comparison; Questionnaire; Cross-cultural; Individualized care